Serum and mucosal antibody-mediated protection and identification of asymptomatic respiratory syncytial virus infection in community-dwelling older adults in Europe - Oner,D; Vernhes,C; Balla-Jhagjhoorsingh,S; Moureau,A; Crabbe,M; Salaun,B; Bastian,AR; Thys,K; De,Smedt J; Ooft,SN; Korsten,K; Adriaenssens,N; et al. (Frontiers in Immunology, 2024)
Introduction: Respiratory syncytial virus (RSV) causes acute respiratory tract infection (ARTI) and reinfects adults throughout life, posing a risk for hospitalization in older adults (>60 years) with frailty and comorbidities.Methods: To investigate serum and mucosal antibodies for protection against RSV infections, baseline serum samples were compared for RSV-pre- and -post-fusion (F) binding, and RSV-A2 neutralizing IgG antibodies between symptomatic RSV-ARTI (N = 30), non-RSV (RSV negative) ARTI (N = 386), and no ARTI (N = 338). Mucosal RSV-pre-F IgA and IgG levels, as well as serum RSV-G IgG antibodies, were analyzed to determine their association with protection from symptomatic RSV-ARTI in a subset study.Results: Using a receiver operating characteristic (ROC) analysis, we established thresholds of 1.4- to 1.6-fold change (FC) for RSV-pre-F and -post-F, and RSV-A2 neutralizing IgG antibodies, respectively, enabling the identification of asymptomatic RSV cases with high sensitivity and specificity (>80% and >90%, respectively). As a result, serum RSV-pre-F, RSV-G IgG, and mucosal pre-F binding IgA antibodies showed correlations with protection against symptomatic RSV infection. RSV-pre-F IgG antibodies were correlated with protection from RSV infections irrespective of the symptoms.Discussion: This study provides insights into antibody-mediated protection for symptomatic RSV infection in a community-dwelling older-adult population and establishes a threshold to identify asymptomatic RSV infection using a data-driven approach.